Literary review of researches on Ferula tenuisecta Korovin — endemic of the Western Tien-Shan - Bekebayeva, M.O.; Nazarbekova, S.T. (KU Publ., 2021)
The study of natural flora and its biodiversity, as well as its conservation, is one of the main tasks in the biological sciences. The threat of extinction of rare, endemic and disappearing species of the flora of Kazakhstan indicates the need to develop scientific foundations and methodological approaches to the conservation, restoration and effective use of their genetic reserves. The flora is characterized by the specific composition, soil and climatic conditions of the region, but many components are poorly studied in terms of their phytochemical and biological activity. The issues of phytochemical studies of plants of the local flora are also listed in the priority directions of the program for the development of pharmaceutical production in the Republic of Kazakhstan. Thus, representatives of genus Ferula (family Apiaceae — Umbelliferae) are known mainly as a source of medicinal properties. Unfortunately, there are few data about useful properties of genus Ferula species in the national and international literature. Ferula tenuisecta Korovin as the medicinal plant is paramount in the production of medicinal preparations due to its chemical composition. Overall, results of the study on Ferula tenuisecta were analyzed in the article. Directions for further study of Ferula tenuisecta were determined.
Батыс Тянь-Шаньның эндемигі Ferula tenuisecta Korovin туралы зерттеу жұмыстарына әдеби шолу
Литературный обзор исследований по эндемику Западного Тянь-Шаня Ferula tenuisecta Korovin
Keywords: Ferula tenuisecta; endem; biological active compounds; cenopopulation; Western Tien-Shan; medicinal properties